Pre-admission acetylsalicylic acid therapy and impact on in-hospital outcome in COVID-19 patients: The ASA-CARE study. (1st December 2021) - Sisinni, Antonio; Rossi, Luca; Battista, Antonio; Poletti, Enrico; Battista, Federica; Battista, Rosa Alessia; Malagoli, Alessandro; Biagi, Andrea; Zanni, Alessia; Sticozzi, Concetta; Comastri, Greta; Marrocco-Trischitta, Massimiliano M.; et al.
Abstract: Background: Patients with coronavirus disease 2019 (COVID-19) exhibit high thrombotic risk. The evidence on a potential independent prognostic role of antiplatelet treatment in those patients is limited. The aim of the study was to evaluate the prognostic impact of pre-admission low-dose acetylsalicylic acid (ASA) in a wide series of hospitalized patients with COVID-19. Methods: This cohort study included 984 COVID-19 patients stratified according to ASA intake before hospitalization: ASA + ( n = 253) and ASA − ( n = 731). Patients were included in ASA + group if they received it daily in the 7 days before admission. 213 (83%) were on ASA 100 mg daily. Primary endpoint was a composite of in-hospital death and/or need for respiratory support upgrade, secondary endpoints were in-hospital death and need for respiratory support upgrade. Results: Mean age was 72 [62; 81] with 69% of male patients. ASA + patients were significantly older, with higher prevalence of comorbidities. No significant differences regarding the degree of respiratory dysfunction were observed. At 30-day Kaplan-Meier analysis, ASA + patients had higher survival free from the primary endpoint and need for respiratory support upgrade, conversely in-hospital death did not significantly differ between groups. At multivariate analysis ASA intake was independently associated with a lower probability of reaching primary endpoint (HR 0.697, 95% C.I. 0.525–0.924; p = 0.012). Conclusions: In COVID-19 patients undergoing hospitalization, pre-admission treatment with ASA is associated with better in-hospital outcome, mainly driven by less respiratory support upgrade. Highlights: Coronavirus disease 2019 (COVID-19) may predispose patients to thrombosis. Antiplatelet therapy may represent an effective therapeutic option. Patients on acetylsalicylic acid therapy suffered less from in-hospital death and/or need for respiratory support upgrade.